GROWTH RATE COMPARISONS OF THREE COLOR MORPHS OF COMMON CARP (Cyprinus carpio L.) CULTURED IN COMMERCIAL FLOATING NET CAGES - Rudhy Gustiano (Zuriat, 2004)
The study aims at establishing possible relationships between growth of weight and color morphs difference of the common carp cultured in floating netcages. Ten floating net-cage (7 m × 7 m × 2 m) were selected from three farms in Cirata Reservoir for studying growth performance. Each cage-net was stocked with 300 kg of 12 cm–16 cm common carp juvenile. The fish was weighed every other week, i.e., at week 0, 2, 4, 6, and 8. The fish in each cage were gathered to one side of the cage with bamboo sheets. Thirty fish for each of three colors (blue, green, and red) were randomly sampled from each cage using a scoop net. The result showed that the green fish was the fastest growing in 2 of the 3 significant cases and blue for 1 case. In most cases color morphs also did not show any differences in the weight regression coefficients. However, there were 5 significant cases where green was always the best followed by the blue one. Thus, there was evidence that the dark color (green and blue) gained weight faster than light one (red). Green and blue colored showed similarity in growth performance based on weight regression coefficient.